Acupuncture in the Management of Intraoperative Nausea and Vomiting - Francisco Gouveia; Carmen Oliveira; Nuno Losa (Medical Association of Pharmacopuncture Institute, 2016)
Intraoperative and postoperative nausea and vomiting (IONV and PONV, respectively) are common complications of anesthesia with significant associated morbidity. Strategies for their prevention and treatment have been organized in pharmacological and nonpharmacological measures. Acupuncture at PC6 has demonstrated efficacy in randomized trials, although evidence regarding its efficacy in treating IONV and PONV has not yet been fully established. We present the case of a patient who underwent peripheral vascular surgery on a limb under a subarachnoid block and who developed IONV refractory to conventional pharmacological therapy. Acupuncture at the PC6 and the TF4 points proved to be an effective alternative treatment to conventional pharmacological treatment and resulted in almost immediate cessation of IONV.